Experimental Study on Strength and Durability Index of Concrete using Mineral Admixture : A Review - Kumar, Ravi; Chandrakar, Bhaskar; Sahu, Pukhraj (International Journal of Scientific Research in Civil Engineering, 2022)
The last few decades are well thought-out to be the era of the self-compacting concrete and thousands of research has been carried out. In India, the development of concrete possessing self-compacting properties is still very much in its initial stages. Over the past couple of years, few attempts were made still the cost of production of such concrete is a challenging issue for the present concrete engineers. In this paper presenting review of literature related to concrete technology.